1992
DOI: 10.1677/joe.0.1350091
|View full text |Cite
|
Sign up to set email alerts
|

Fluid balance, electrolyte profiles and plasma parathyroid hormone concentrations in ewes treated with epidermal growth factor

Abstract: The infusion of low doses of epidermal growth factor (EGF) into lactating ewes stimulates water intake and urine volume. The plasma concentrations and daily output of various electrolytes in milk and urine are also affected. We have investigated this further by recording the effects of EGF infusion on fluid balance, electrolyte profiles and plasma concentrations of glucose and parathyroid hormone (PTH) in non-pregnant, non-lactating ewes. Twenty-four animals (n = 8 per group) received infusions of 100 ml salin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Renal artery infusion of EGF in sheep produced natriuresis and diuresis, suggesting a tubular effect [25]. When administered basolaterally to isolated rabbit cortical collecting duct, EGF inhibited sodium transport by inhibiting the epithelial sodium channel (ENaC) [26, 27], and also inhibited the hydroosmotic effect of vasopressin [28].…”
mentioning
confidence: 99%
“…Renal artery infusion of EGF in sheep produced natriuresis and diuresis, suggesting a tubular effect [25]. When administered basolaterally to isolated rabbit cortical collecting duct, EGF inhibited sodium transport by inhibiting the epithelial sodium channel (ENaC) [26, 27], and also inhibited the hydroosmotic effect of vasopressin [28].…”
mentioning
confidence: 99%
“…Thus, intravenous infusion of EGF into lactating ewes stimulated urine volume increase by 29–134%, and this effect was dose-related [31]. In ewes, the polyuria was found to occur on the first day of EGF infusion [23, 31]. The mechanism behind the EGF-induced polyuria, however, has not been fully elucidated [27].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism behind the EGF-induced polyuria, however, has not been fully elucidated [27]. Previously, it has been found that active sodium reabsorption in perfused isolated rabbit cortical collecting ducts are inhibited by EGF and that EGF can regulate membrane transport events in vitro [31]. Sack and Talor [32] already in 1988 suggested a physiological role for EGF in the proximal tubules and medullary portions of the rabbit nephron, due to the presence of low- and high-affinity binding sites for EGF.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, i.v. infusion of low doses of EGF into early-lactating (Gow & Moore, 1992), anoestrous (Gow, Wilkinson, Silvapulle & Moore, 1992) and ovariectomized (Gow, Phillips, Chandler & Moore, 1993) ewes was shown to stimulate profound increases in water intake and urine volume and increased the urinary excretion of sodium (Gow et al 1992(Gow et al , 1993. In these studies, all animals had access to an ad libitum supply of water and thus could maintain normal fluid balance.…”
mentioning
confidence: 99%
“…On the other hand, if EGF acted directly on the kidney, resulting in polyuria (with secondary polydipsia), water restriction would result in progressive dehydration. The doses of EGF which have been previously reported to stimulate profound increases in water intake and urine volume in sheep include 0 5 mg day' (Gow & Moore, 1992), 5 or 10 ,sg (kg live weight)' day' (Gow et at. 1992) and 10 or 20 jcsg h1 (Gow et al 1993).…”
mentioning
confidence: 99%